Cuadro de clasificación para el Archivo Diocesano de Salamanca - Manzano García, Maribel (Revista española de derecho canónico, 2013)
In 2006, the Diocese of Salamanca asked for helping to the Universidad Pontificia de Salamanca to raise some objectives in their Diocesan Archive, in order to obtain funds for the archive. One of the first and most important activities was to elaborate the classification scheme, this instrument is the object of this article